2022
DOI: 10.3389/fnhum.2021.773091
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Virtual Height Exposure on Postural Control and Psychophysiological Stress Are Moderated by Individual Height Intolerance

Abstract: Virtual reality (VR) enables individuals to be exposed to naturalistic environments in laboratory settings, offering new possibilities for research in human neuroscience and treatment of mental disorders. We used VR to study psychological, autonomic and postural reactions to heights in individuals with varying intensity of fear of heights. Study participants (N = 42) were immersed in a VR of an unprotected open-air elevator platform in an urban area, while standing on an unstable ground. Virtual elevation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…An intermittent control of quiet upright standing ( 73 76 ) would likely favour increase in Sway Area rather than Path Length. When the conditions are unstable (as in EC Foam) and the subjects search for a safe posture, the association between Sway Area and Path Length (as assessed by the determination coefficient) improves but remains moderate, being probably dependent on the idiosyncratic behaviour of the single participants ( 77 ). All in all, the measures of Sway Area and Path Length cannot be considered equivalent, or redundant.…”
Section: Discussionmentioning
confidence: 99%
“…An intermittent control of quiet upright standing ( 73 76 ) would likely favour increase in Sway Area rather than Path Length. When the conditions are unstable (as in EC Foam) and the subjects search for a safe posture, the association between Sway Area and Path Length (as assessed by the determination coefficient) improves but remains moderate, being probably dependent on the idiosyncratic behaviour of the single participants ( 77 ). All in all, the measures of Sway Area and Path Length cannot be considered equivalent, or redundant.…”
Section: Discussionmentioning
confidence: 99%
“…First, we aim to replicate previous findings that the perception of postural instability onset is not significantly slower than that of an auditory reference stimulus [3,4]. Second, we hypothesize that presenting a visually threatening scene via virtual reality (VR) will reduce any perceived delay between postural instability onset and an auditory reference stimulus compared to a non-threatening environment, based on observed behavioral and psychological changes at both physical and virtual heights [7,11-18]. Finally, we anticipate that participants will exhibit improved precision or a reduction in the variability of their responses, resulting in a decreased just noticeable difference (JND) in their TOJ tasks when exposed to a virtual height.…”
Section: Introductionmentioning
confidence: 82%
“…On the other hand, the JND (precision) of responses markedly differed between the eyes-open and VR conditions. Research has consistently shown that VR and threatening visual scenes can induce psychological effects such as increased arousal, heightened anxiety, and diminished confidence in balance [7,11-18]. These effects likely sharpen an individual’s attention, which, while not affecting PSS, has been found to improve the precision (reduce JND) of TOJ responses [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence suggests that psychological factors, such as fear, influence postural control. The emotional states affect the sensorimotor processes underlying balance control and can significantly influence postural stability ( Teggi et al, 2019 ), which is especially evident in individuals with fear of falling ( Davis et al, 2009 ) and fear of heights ( Bzdúšková et al, 2022 ). It has been reported that about 30% of the adult population suffers from visual height intolerance, which reduces the quality of life and causes various constraints such as avoidance of heights ( Huppert et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%